Low-noise PA6 composite material and preparation method thereof

By using the modification technology of porous graphite and grafted polyether segments in PA6 composite materials, the problem of noise generated during friction is solved, and the material is low noise, long life and high stability are achieved.

CN119391174APending Publication Date: 2025-02-07NINGBO RUILONG NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411574578.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

During use, PA6 engineering plastics produce noise due to friction. Traditional modification solutions such as the addition of polytetrafluoroethylene will lead to the loss of noise reduction effect.

Method used

Porous graphite is used as a noise reduction additive and polyether segments are grafted on its surface. The hydrophobicity and interface binding force of porous graphite are improved through modification treatment to reduce noise generation.

Benefits of technology

It effectively reduces the friction and wear of PA6 composite materials, extends the service life of the material, and improves dimensional stability and chemical stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a low-noise PA6 composite material and a preparation method thereof, the PA6 composite material is prepared from the following raw materials in parts by mass: 40-90 parts of PA6 resin, 1-6 parts of a noise reduction auxiliary agent, 0.1-1 part of an antioxidant, 0.1-1 part of a lubricant and 0-60 parts of glass fibers, and the noise reduction auxiliary agent is porous graphite. The pore structure of the porous graphite can enhance the interface bonding force with the PA6 base material, and the compression resilience can help the PA6 base material to disperse stress and reduce stress concentration when the PA6 base material is subjected to external force, so that the surface abrasion phenomenon of the composite material is reduced, and noise is reduced. And after the porous graphite is subjected to graft modification treatment by the polyether chain segment, the stability is improved, the flexibility and fluidity of the molecular chain of the material are also improved by introducing the flexible chain segment, the friction property of the material is reduced, and the service life of the low-noise PA6 composite material is further prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of PA6 engineering plastics, and in particular to a low-noise PA6 composite material and a preparation method thereof. Background Art

[0002] PA6 (polycaprolactam), as an important engineering plastic, is widely used in various fields, especially in the fields of electronics and automobiles, due to its good mechanical properties, chemical resistance and molding and processing performance. With the current technological innovation, various fields have put forward more functional requirements for PA6 to further improve the volatility and poor light resistance of PA6 during use, and to extend the service life of PA6.

[0003] In the actual application of PA6, when the components made of PA6 material come into contact with metal, leather or other plastic parts, they will produce noise due to friction, thus affecting the actual use. To solve this problem, the traditional modification scheme is to add noise reduction additives such as polytetrafluoroethylene to reduce the friction coefficient between other components, thereby reducing the generation of noise. However, polytetrafluoroethylene will precipitate after long-term use, thus losing the noise reduction effect. Summary of the invention

[0004] In order to solve the noise problem of PA6 during use, the present invention provides a low-noise PA6 composite material and a preparation method thereof.

[0005] In a first aspect, the present invention provides a low-noise PA6 composite material, comprising the following raw materials in parts by weight: 40-90 parts of PA6 resin; 1 to 6 parts of noise reduction agent; Antioxidant 0.1-1 part; Lubricant 0.1-1 part; Glass fiber 0-60 parts; The noise reduction agent is porous graphite.

[0006] Preferably, the intrinsic viscosity of the PA6 resin is 2.0 to 2.8 dL / g.

[0007] Preferably, the antioxidant includes a combination of one or more of antioxidant 1098, antioxidant 1010, antioxidant 168 and antioxidant 9228.

[0008] Preferably, the lubricant comprises a combination of one or more of calcium stearate, calcium montanate, ethylene bis stearamide and pentaerythritol stearate. Preferably, the glass fiber is chopped glass fiber; the monofilament diameter of the chopped glass fiber is 7 to 14 μm.

[0009] Preferably, the carbon content of the porous graphite is ≥99.9% and the specific surface area is ≥10m 2 / g.

[0010] By adopting the above technical scheme, the present invention adopts porous graphite as a noise reduction agent for PA6 composite materials. On the one hand, graphite itself has a layered structure that can slide against each other, and can reduce the friction and wear of the PA6 matrix after being mixed with the PA6 resin. As a special type of graphite, porous graphite has a larger specific surface area and porosity, which can reduce the friction of the matrix while increasing the contact area between the porous graphite and the PA6 substrate, thereby improving the interfacial bonding force between the two and reducing the possibility of the noise reduction agent precipitating from the substrate. Moreover, the pore structure of the porous graphite can form a locking effect with the molecular chain of the PA6 resin, so that the porous graphite will not easily move or detach from the substrate during production and actual use, causing the substrate to lose its noise reduction effect, thereby extending the stability of the low-noise PA6 composite material and extending its service life.

[0011] On the other hand, the pore structure of porous graphite still has compression resilience, which can help the PA6 substrate disperse stress when subjected to external forces, reduce the formation of local high stress areas, thereby reducing material surface wear, and then reduce the friction between the composite material and other materials caused by wear, thereby reducing the generation of noise.

[0012] At the same time, in order to enhance the mechanical properties of the PA6 composite material including shear resistance and impact resistance, the PA6 composite material of the present invention can also add glass fiber to adjust the strength of the material, and the use of short-cut fibers can better enhance the material performance to meet the needs of various fields for PA6 materials.

[0013] Preferably, polyether segments are grafted onto the surface of the porous graphite.

[0014] The special pore structure of porous graphite can reduce the friction and wear of the substrate while enhancing the interfacial force between it and the PA6 substrate. However, this pore structure also allows air and moisture to enter and diffuse freely. The capillary force generated by the pores can adsorb and retain moisture in the air. The oxygen-containing functional groups on the graphite surface can also form hydrogen bonds with water molecules to enhance the hygroscopic performance. The PA6 resin itself has certain hygroscopic properties, which will further affect the dimensional stability of the PA6 composite material. By adopting the above technical solution, the porous graphite is modified and polyether segments are grafted on the surface.

[0015] The introduction of polyether segments can form a hydrophobic protective film on the surface of porous graphite, reducing the direct contact between porous graphite and water molecules, making it difficult for water molecules to adsorb on the surface of porous graphite, thereby reducing the hygroscopicity of graphite. At the same time, the three-dimensional barrier structure formed by the polyether segments also prevents water molecules from entering the pore structure of porous graphite, reducing the ability of graphite to absorb water, and can also enhance the chemical stability of graphite materials, making them more durable in humid environments and improving the dimensional stability of the overall composite material.

[0016] Preferably, the raw materials of the porous graphite grafted polyether chain segment include acidified porous graphite and propylene glycol block polyether in a mass ratio of 1:(0.4-0.6).

[0017] Preferably, the molecular weight of the propylene glycol block polyether is 1900-2400.

[0018] By adopting the above technical scheme, in order to further achieve the improvement effect of polyether segments on porous graphite, propylene glycol block polyether is used to graft and modify the porous graphite. The grafted polyether segments can significantly reduce the material's absorption capacity for water molecules, and propylene glycol block polyether is a flexible high molecular polymer material. In addition to improving the hydrophobic properties of the material, it can also improve the lubricity between the porous graphite and the PA6 substrate, and can form a certain steric hindrance between the PA6 substrate, hindering the close stacking of the PA6 segments, thereby reducing the direct contact between molecules and reducing the friction of the PA6 composite material.

[0019] At the same time, the introduction of flexible segments can also improve the fluidity between segments inside the PA6 composite material, so that the material can disperse stress more evenly when subjected to external forces, reduce local friction loss, and thus reduce noise. In addition, the introduction of polyether segments can also enhance the interfacial force between porous graphite and PA6 molecular chains, improve the bonding force of porous graphite in the PA6 matrix, and prevent precipitation problems during production or actual use.

[0020] Preferably, the porous graphite grafted polyether segment is prepared according to the following method: Preparation of acidified porous graphite: adding porous graphite to a strong acid solution, raising the temperature to 35-45°C, stirring and refluxing for 12-24 hours to obtain the acidified porous graphite; Preparation of porous graphite grafted polyether chain segment: add thionyl chloride to the solvent, mix well, then add acidified porous graphite, disperse evenly, reflux at 60-70°C for 24-26h, reduce pressure and filter after reflux, add the obtained product to the solvent, disperse evenly, add propylene glycol block polyether under ice bath conditions, increase the temperature to 100-120°C, stir the reaction for 10-12h, and finally wash and dry to obtain the porous graphite grafted polyether chain segment.

[0021] Preferably, the strong acid solution includes concentrated sulfuric acid, concentrated nitric acid, or a combination of both.

[0022] Preferably, the solvent includes one or more of N,N-dimethylformamide, N,N-dimethylacetamide and hexamethylphosphoric triamide.

[0023] By adopting the above technical solution, the porous graphite is first pretreated before modification and grafting, and the number of oxygen-containing functional groups of the porous graphite can be increased by the action of strong acid, thereby increasing the grafting rate of the propylene glycol block polyether on the porous graphite. Then, the hydroxyl groups and oxygen-containing functional groups on the porous graphite are chlorinated under the action of thionyl chloride to facilitate the reaction with the hydroxyl groups in the propylene glycol block polyether, thereby obtaining modified grafted porous graphite.

[0024] In a second aspect, the present invention provides a method for preparing a low-noise PA6 composite material, comprising the following process steps: S1. Dry the PA6 resin at 80-100°C for 4-6h; S2. Weigh the dried PA6 resin, noise reduction agent, antioxidant and lubricant according to the corresponding mass parts and mix them evenly to obtain a premix; S3. The premix is ​​melt-extruded at 220-250° C., cooled and granulated to obtain a low-noise PA6 composite material.

[0025] Preferably, in the step S3, glass fiber is side-fed during the melt extrusion process.

[0026] In summary, this application has the following beneficial effects: 1. The low-noise PA6 composite material of the present invention uses porous graphite as a noise reduction agent. Graphite itself has a good ability to improve the friction performance of the PA6 substrate and reduce wear. At the same time, the pore structure of the porous graphite can also enhance the interface bonding force between the PA6 substrate and the porous graphite. The compression rebound performance can help the PA6 substrate to disperse stress when subjected to external force, reduce stress concentration, thereby reducing the surface wear of the composite material and reducing the generation of noise.

[0027] 2. The porous graphite surface adopted in the present invention is grafted with polyether segments. Although the porous graphite can reduce the friction performance of the composite material and reduce the formation of noise from multiple angles, the porous graphite and the PA6 substrate itself have strong hygroscopicity, which will affect the dimensional stability of the material and thus reduce the application range of the material. The porous graphite modified with polyether segments, especially the porous graphite modified with propylene glycol block polyether, has a certain hydrophobicity, and the formed three-dimensional barrier can improve the dimensional stability of the composite material. In addition, the introduction of polyether segments can improve the interfacial force between the porous graphite and the PA6 substrate, and can also improve the flexibility and fluidity of the molecular chain of the material, reduce the friction of the material, and further extend the service life of the low-noise PA6 composite material. DETAILED DESCRIPTION

[0028] Preparation Example of Porous Graphite; Preparation Example 1, a porous graphite is prepared according to the following method: 10g porous graphite (carbon content ≥ 99.9%, specific surface area ≥ 10m 2 / g) was added into 500mL concentrated nitric acid solution, the temperature was raised to 40°C, and the mixture was stirred and refluxed for 16h to obtain acidified porous graphite; 200 mL of thionyl chloride was added to 50 mL of N, N-dimethylformamide, and after mixing evenly, 10 g of the acidified porous graphite obtained above was added, and after being evenly dispersed, the mixture was refluxed at 65°C for 24 h. After the reflux was completed, the product was filtered under reduced pressure and added to 500 mL of N, N-dimethylformamide. After being evenly dispersed, 50 g of propylene glycol block polyether (average molecular weight of 1900, model L35 propylene glycol block polyether) was added under ice bath conditions. The temperature was raised to 120°C, and the reaction was stirred for 12 h. Finally, the porous graphite grafted polyether segment was obtained after washing and drying.

[0029] Preparation Example 2, a porous graphite, is different from Preparation Example 1 only in that the added amount of propylene glycol block polyether is 40 g, the average molecular weight of the propylene glycol block polyether is 2400, and the model is L45 propylene glycol block polyether.

[0030] Preparation Example 3, a porous graphite, is different from Preparation Example 1 only in that the added amount of propylene glycol block polyether is 60 g.

[0031] Preparation Example 4, a porous graphite, is different from Preparation Example 1 only in that the added amount of propylene glycol block polyether is 30 g.

[0032] Preparation Example 5, a porous graphite, is different from Preparation Example 1 only in that the added amount of propylene glycol block polyether is 70 g.

[0033] Preparation Example 6: A porous graphite is prepared according to the following method: Add 200 mL of thionyl chloride to 50 mL of N,N-dimethylformamide, mix well, and then add 10 g of porous graphite (carbon content ≥ 99.9%, specific surface area ≥ 10 m 2 / g), dispersed evenly and refluxed at 65°C for 24h. After the reflux, the product was added into 500mL N,N-dimethylformamide and dispersed evenly. 50g propylene glycol block polyether (average molecular weight of 1900, model L35 propylene glycol block polyether) was added under ice bath condition. The temperature was raised to 120°C, stirred for 12h, and finally washed and dried to obtain porous graphite grafted polyether segments.

[0034] Preparation Example 7, a porous graphite, prepared according to the following method: 10g porous graphite (carbon content ≥ 99.9%, specific surface area ≥ 10m 2 / g) was added into 500mL concentrated nitric acid solution, the temperature was raised to 40°C, and the mixture was stirred and refluxed for 16h to obtain the acidified porous graphite. Example

[0035] Example 1, a low-noise PA6 composite material is prepared according to the following process steps: S1. Dry PA6 resin (intrinsic viscosity 2.2 dL / g) at 80°C for 6 h; S2. Weigh 6.8 kg of dried PA6 resin and 0.5 kg of porous graphite (carbon content ≥ 99.9%, specific surface area ≥ 10m 2 / g), 0.01kg antioxidant 1098, 0.02kg antioxidant 168 and 0.03kg pentaerythritol stearate were uniformly mixed to obtain a premix; S3. The premix is ​​melt-extruded at 220-250°C, and 3kg of chopped glass fiber is added to the side feed, and a low-noise PA6 composite material is obtained after cooling and granulation. The melt extrusion process uses a twin-screw extruder with a length-to-diameter ratio of 40:1, and the extrusion temperature of each section is set to 240, 240, 240, 230, 225, 220, 220, 235, 235, 250.

[0036] Example 2 and Example 3 are low-noise PA6 composite materials, which differ from Example 1 only in that the ratio of the raw materials is adjusted, as shown in Table 1: Table 1 Formula table of Example 1 to Example 3

[0037] Example 4 is a low-noise PA6 composite material, which is different from Example 1 only in that the added amount of porous graphite is 0.1 kg.

[0038] Example 5 is a low-noise PA6 composite material, which is different from Example 1 only in that the amount of porous graphite added is 0.6 kg.

[0039] Example 6 is a low-noise PA6 composite material, which is different from Example 1 only in that the porous graphite prepared in Preparation Example 1 is used to replace the porous graphite.

[0040] Example 7, a low-noise PA6 composite material, differs from Example 1 only in that the porous graphite is replaced by an equal amount of the porous graphite prepared in Preparation Example 2.

[0041] Example 8 is a low-noise PA6 composite material, which is different from Example 1 only in that the porous graphite is replaced by an equal amount of the porous graphite prepared in Preparation Example 3.

[0042] Example 9 is a low-noise PA6 composite material, which is different from Example 1 only in that the porous graphite is replaced by an equal amount of the porous graphite prepared in Preparation Example 4.

[0043] Example 10 is a low-noise PA6 composite material, which is different from Example 1 only in that the porous graphite prepared in Preparation Example 5 is used to replace the porous graphite.

[0044] Example 11 is a low-noise PA6 composite material, which is different from Example 1 only in that the porous graphite is replaced by an equal amount of the porous graphite prepared in Preparation Example 6.

[0045] Example 12, a low-noise PA6 composite material, is different from Example 1 only in that the porous graphite is replaced by an equal amount of the porous graphite prepared in Preparation Example 7.

[0046] Comparative Example; Comparative Example 1, a low-noise PA6 composite material, differs from Example 1 only in that the amount of porous graphite added is 0.05 kg.

[0047] Comparative Example 2 is a low-noise PA6 composite material, which is different from Example 1 only in that the amount of porous graphite added is 0.8 kg.

[0048] Comparative Example 3 is a low-noise PA6 composite material, which is different from Example 1 only in that porous graphite is not added.

[0049] Comparative Example 4 is a low-noise PA6 composite material, which is different from Example 2 only in that porous graphite is not added.

[0050] Comparative Example 5 is a low-noise PA6 composite material, which is different from Example 1 only in that the porous graphite is replaced by an equal amount of polytetrafluoroethylene.

[0051] Performance test; 1. Mechanical properties test: (1) Tensile property test: According to the relevant records in ISO 527-1-2012 "Determination of tensile properties of plastics Part 1: General" and ISO 527-2-2012 "Test method for tensile properties of plastics", the tensile strength of the low-noise PA6 composite materials obtained in the examples and comparative examples was tested, wherein the test rate was 5 mm / min; (2) Impact performance test: According to the relevant records in ISO 179-1-2010 "Determination of simply supported beam impact strength of plastics", the simply supported beam notched impact strength of the low-noise PA6 composite materials obtained in the examples and comparative examples was tested, wherein the impact energy was 4J.

[0052] The above test results are shown in Table 2.

[0053] 2. Noise reduction performance test: According to the relevant records in the VDA 230-206-2005 material stick-slip behavior test standard, the noise reduction effects of the low-noise PA6 composite materials obtained in the embodiments and the comparative examples were compared by testing the RPN (risk priority number) under different pressures and speeds, wherein RPN≤3 indicates no noise risk, 3<RPN≤6 indicates a medium noise risk, and RPN>6 indicates a high noise risk; and an aging test (placing the samples in a constant temperature box at 90°C for 500h) was also performed to compare the long-term noise reduction effects of the materials.

[0054] The following four test conditions are set up: Condition 1: pressure 10N, speed 1mm / s; Condition 2: pressure 10N, speed 4mm / s; Condition 3: pressure 40N, speed 1mm / s; Condition 4: pressure 40N, speed 4mm / s.

[0055] The above test results are shown in Table 3.

[0056] Table 2 Mechanical properties test results

[0057] Table 3 Noise reduction performance test

[0058] According to Table 2 and Table 3, combined with Example 1, Example 2 to Example 5, it can be seen that the noise reduction performance test results of Example 2 to Example 5 are similar to those of Example 1, with no significant difference, and the mechanical properties of Example 4 and Example 5 are not significantly different from those of Example 1, and the mechanical properties of Example 2 and Example 3 are respectively decreased and increased compared with Example 1. The reason may be that compared with Example 1, Example 2 to Example 5 only changed the raw materials and the ratio of raw materials within the required range, so the noise reduction performance of the obtained composite material is not significantly different from that of Example 1, and the change in mechanical strength of Example 2 and Example 3 is mainly due to the different added glass fiber content. As the glass fiber content increases, the mechanical strength of the material also increases, and both fluctuate within a reasonable range.

[0059] Combining Example 1, Example 6, and Example 7 to Example 12, it can be seen that the mechanical strength and noise reduction performance of Example 6 to Example 12 are improved compared with Example 1, among which Example 6 to Example 8 are improved most significantly. The reason may be that Example 6 uses porous graphite modified by grafting of polyether segments compared with Example 1, and its stability is improved compared with Example 1, the interfacial force between the material and the PA6 substrate is improved, and the link density between the molecular chains inside the material is improved, thereby increasing the mechanical strength of the composite material obtained, and the introduction of polyether flexible segments will also reduce the friction coefficient of the material, increase the wear resistance of the material, reduce material wear, and prevent the generation of noise. In addition, under the synergistic effect of porous graphite and polyether segments, the bonding force between PA6 and porous graphite can be enhanced, and the service life of the low-noise PA6 composite material can be improved, and the effect will not be easily lost under harsh conditions. Compared with Example 6, Examples 7 and 8 only change the raw material ratio of porous graphite in the grafting process within the required range, which has little effect on the performance of the obtained material. Compared with Example 6, Example 9 and Example 10 changed the amount of propylene glycol block polyether added during the grafting modification process. The improvement effect of the material decreased with the reduction of the amount added, and the increase of the amount added would increase the spatial resistance between the materials, which is not conducive to the improvement of performance and the combination of porous graphite and PA6 substrate. In Example 11, the porous graphite was not acidified before the propylene glycol block polyether was directly grafted. The decrease in the content of oxygen-containing functional groups on the surface of the porous graphite will affect the grafting rate of the polyether segment in the next step. The decrease in the content of the polyether segment will reduce the modification effect of the material accordingly. In Example 12, no polyether segment was grafted, but after acidification, the increase in oxygen-containing functional groups can also increase the interfacial force between the porous graphite and the PA6 substrate to a certain extent.

[0060] Combining Example 1 and Comparative Examples 1 to 4, it can be seen that the mechanical properties and noise reduction performance of Comparative Examples 1 to 4 are significantly reduced compared to Example 1. The reason may be that the amount of porous graphite added in Comparative Examples 1 and 2 is changed. The amount of porous graphite added in Comparative Example 1 is reduced, and the corresponding improvement of the noise reduction performance of the material is reduced. After long-term heat aging treatment, the noise reduction performance is significantly reduced, and the amount of porous graphite added in Comparative Example 2 is increased, which will cause the graphite to agglomerate internally, which is not conducive to the improvement of performance. No porous graphite is added in Comparative Examples 3 and 4. On the one hand, the reinforcement effect of porous graphite is reduced, and on the other hand, the effect of noise reduction additives is reduced, and the noise reduction effect of the material is significantly reduced.

[0061] Combining Example 1 and Comparative Example 5, it can be seen that the mechanical properties and noise reduction performance of Comparative Example 5 are lower than those of Example 1. The reason may be that polytetrafluoroethylene is used as a noise reduction additive in Comparative Example 5. On the one hand, compared with graphite, polytetrafluoroethylene has a poorer enhancement effect on the mechanical properties of the material. On the other hand, although polytetrafluoroethylene has a certain noise reduction effect in the initial stage of preparation, after long-term heat aging treatment, polytetrafluoroethylene will gradually precipitate to the surface of the material, thereby causing the material to lose its noise reduction effect, so the noise reduction performance decreases significantly after aging.

[0062] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A low-noise PA6 composite material, characterized in that: Including the following raw materials by mass: 40-90 parts of PA6 resin; 1 to 6 parts of noise reduction agent; Antioxidant 0.1-1 part; Lubricant 0.1-1 part; Glass fiber 0-60 parts; The noise reduction agent is porous graphite.

2. The low-noise PA6 composite material according to claim 1, characterized in that: The surface of the porous graphite is grafted with polyether segments.

3. The low-noise PA6 composite material according to claim 2, characterized in that: The raw materials of the porous graphite grafted polyether chain segment include acidified porous graphite and propylene glycol block polyether in a mass ratio of 1: (0.4-0.6).

4. The low-noise PA6 composite material according to claim 3, characterized in that: The molecular weight of the propylene glycol block polyether is 1900-2400.

5. The low-noise PA6 composite material according to claim 3, characterized in that: The porous graphite grafted polyether segment is prepared according to the following method: Preparation of acidified porous graphite: adding porous graphite to a strong acid solution, raising the temperature to 35-45°C, stirring and refluxing for 12-24 hours to obtain the acidified porous graphite; Preparation of porous graphite grafted polyether chain segment: add thionyl chloride to the solvent, mix well, then add acidified porous graphite, disperse evenly, reflux at 60-70°C for 24-26h, reduce pressure and filter after reflux, add the obtained product to the solvent, disperse evenly, add propylene glycol block polyether under ice bath conditions, increase the temperature to 100-120°C, stir the reaction for 10-12h, and finally wash and dry to obtain the porous graphite grafted polyether chain segment.

6. The low-noise PA6 composite material according to claim 1, characterized in that: The antioxidant includes a combination of one or more of antioxidant 1098, antioxidant 1010, antioxidant 168 and antioxidant 9228.

7. The low-noise PA6 composite material according to claim 1, characterized in that: The lubricant includes a combination of one or more of calcium stearate, calcium montanate, ethylene bis stearic acid amide and pentaerythritol stearate.

8. The low-noise PA6 composite material according to claim 1, characterized in that: The glass fibers are chopped glass fibers; the monofilament diameter of the chopped glass fibers is 7 to 14 μm.

9. A method for preparing a low-noise PA6 composite material according to any one of claims 1 to 8, characterized in that: The process steps include: S1. Dry the PA6 resin at 80-100°C for 4-6h; S2. Weigh the dried PA6 resin, noise reduction agent, antioxidant and lubricant according to the corresponding mass parts and mix them evenly to obtain a premix; S3. The premix is ​​melt-extruded at 220-250° C., cooled and granulated to obtain a low-noise PA6 composite material.

10. The method for preparing the low-noise PA9 composite material according to claim 9, characterized in that: In the step S3, glass fibers are side-fed during the melt extrusion process.